Step-by-step explanation:
You need to solve for x.
You can do that by either setting both of the equations equal to each other. or Solve each one separately and subtract the EG equation from the EW to get GW
Hello!
To solve this problem, we will use a system of equations. We will have one number be x and the other y. We will use substitutions to solve for each variable.
x+y=9
x=2y-9
To solve for the two numbers, we need to solve the top equation. The second equation shows that x=2y-9. In the first equation, we can replace 2y-9 for x and solve.
2y-9+y=9
3y-9=9
3y=18
y=6
We now know the value of y. Now we need to find x. We can plug in 6 for y in the second equation to find x.
x=2·6-9
x=12-9
x=3
Just to check, we will plug these two numbers into the first equation.
3+6=9
9=9
Our two numbers are three and six.
I hope this helps!
It would be 2 root 2
bc it simplifies to root 2 and root 4
root 4 simplifies to 2
so its 2√2